Desempenho técnico e econômico da produção de milho e sorgo para silagem e soja em sucessão em sistema irrigado de integração lavoura-pecuária no cerrado - Costa, Nídia Raquel [UNESP] (2014)
As an alternative for increasing productivity of sustainable production systems, the Crop-Livestock Integration System under no-tillage. Thus, the present study aimed to evaluate in an Oxisol under irrigated conditions in the Cerrado region: 1) The performance and quality of silage produced by corn and sorghum production systems, intercropped or not with Urochloa brizantha var. Xaraés and Megathyrsus maximum var. Tanzania; 2) evaluate each harvest, from autumn to spring, the forage yield and nutritional value by the effect of the application or not of nitrogen (70 kg ha-1 N cutting-1 - source of urea), after silage harvest; 3) in the last cut, verify beyond forage productivity, the macronutrient levels and straw decomposition and fodder after spring desiccation and effect on soybean yield in succession; 4) evaluate throughout the systems production, changes in chemical and physical soil properties, besides the accumulation of carbon in the 0 to 0.20 m layer at the end of each production cycle; 5) evaluate the economic performance of the Crop-Livestock Integration (CLI) system under no-tillage (NT), to verify the sustainability and profitability of each system during the agricultural period 2010/2011, 2011/2012 and 2012/2013. It was found that the consortium of corn and sorghum with Xaraés and Tanzania grasses are viable for the production of silage in quantity and chemical composition quality, as much as, the single crop cultivation in no-tillage system in the Cerrado. Nitrogen fertilization increased dry matter yield, with improvement of the chemical and nutritional quality of grasses, regardless of the methods of cultivation. Similarly, the Xaraés and Tanzania grasses, resulted in adequate ground cover, up to 90 days after the management of desiccation and cutting, especially when fertilized with nitrogen. In irrigated conditions in the Cerrado, aiming the increase of soybean yield, it is ...